Influence Of Microencapsulated As A Concrete Self-Healing Agent Containing Sodium Silicate - Rawawi, Rawaidatul Alifah Mohd (Universiti Sains Malaysia, 2022)
Concrete is the most popular building material that is widely used around the world. However, the weakness of concrete is prone to cracking due to its brittleness behavior. Therefore, self-healing concrete was invented and introduced to prevent and limit the impact of cracks on the concrete. The aim of this investigation is to carry out a systematic literature review on the influence of microencapsulated as a concrete self-healing agent containing sodium silicate. Through this systematic review, the recent findings and gap of knowledge would be able highlighted and underlined for further investigation. The objectives of this systematic review is to investigate the contributing factors in the mechanism of microencapsulated and the performance of sodium silicate as a concrete self-healing agent. In addition, the gap of knowledge using microencapsulated containing sodium silicate as a concrete self-healing agent will be identified and classified. There were 27 articles have been explored and surveyed from Science Direct, Scopus and Google Scholar to be reviewed. The systematic review should follow the protocol with distinctly delineated steps to provide a clear understanding of research questions, and ensures transparency and reproducibility. In this review, the effectiveness of delivering liquid healing agents via microcapsules is discussed. Size, shape and dosage of capsules of microcapsules affecting quantity of liquid healing agent released into cracks. Moreover, the mechanical properties of microcapsules also explained in the discussion because it will affect the mechanism of microcapsules. Furthermore, the election of sodium silicate as healing agent give many advantages towards self-healing concrete. Thus, microcapsules with help of sodium silicate as a core can enhance the compressive and flexural strength of the crack concrete. Microcapsules for self-healing cementitious materials could benefit from this review's findings.